ISSUES OF ONLINE IMPLEMENTATION OF TAX AUDIT FROM UZBEKISTAN - Фискал институт катта ўқитувчи; Фискал институт талабаси (Web of Journals Publishing, 2024)
The article examines the procedure for conducting a tax audit and considers the issues of introducing an online tax audit. In this, the calculation of taxes and fees for a certain period and checking their correctness is aimed at the correct calculation of the tax audit procedures and measures for the correct and fair tax audit. In addition , s The audit is aimed at correct and reasonable checking of the tax offices directly without going to the place from a distance, and thus making the right decision on their behalf and eliminating the shortcomings by evaluating the mistakes and shortcomings of the taxpayers.
Keywords: Taxpayers , tax agents, tax audit, tax audits, cameral tax audit, mobile tax audit, temporary suspension of accounts, financial and tax reports.